Nicotiana tabacum var. Virginia Bio Oil-based Pyrolysis Extraction Have Prominence Antimicrobial Potential Compared to Ethanol Heat Reflux Extraction (EHRE) - Andri Pramesyanti Pramono; Basra Ahmad Amru; Halimah Anggi Rahmani; Sheila Azelya Fernanda; Yudhi Nugraha; Muhammad Yusuf Arya Ramadhan; Andre Fahriz Perdana Harahap; Ahmad Fauzantoro; Nasihin Saud Irsyad; Meiskha Bahar; Oktania Sandra Puspita; Fajriati Zulfa; Kori Yati; Mahdi Jufri; Misri Gozan (Bogor Agricultural University, Indonesia, 2022)
Tobacco leaf contains antibacterial secondary metabolite compounds, such as phenol, alkaloids, and essential oils. This study compares the potential antibacterial effects of Indonesian tobacco leaf extracted using the heat reflux method (producing an extract) and pyrolysis method (providing a bio-oil). The tobacco leaf extract was challenged against Staphylococcus aureus ATCC 25923, Enterococcus faecalis ATCC 29212, Escherichia coli ATCC 25922, Pseudomonas aeruginosa ATCC 27853. The bio-oil from the pyrolysis method showed inhibitory Kirby Bauer zones higher than those of the extract from heat reflux method, with the maximum results in the pyrolysis method indicating zones of 6.35 mm (S. aureus), 5.90 mm (E. faecalis), 3.97 mm (E. coli), and 5.025 mm (P. aeruginosa). Further study analyzed the effectiveness of the disc and well diffusion antibacterial test methods for measuring the antibacterial effect of bio-oils against Escherichia coli ATCC 25922 and Pseudomonas aeruginosa ATCC 27853. The bio-oil used in the well diffusion test method showed the most significant antibacterial effectiveness. It showed the biggest inhibition zone, with a maximum of 11.65 mm and 8.90 mm for E. coli and P. aeruginosa. Our results showed Nicotiana tabacum var. Virginia Bio Oil from Ponorogo (Indonesia) is a strong potential antimicrobial, especially using well diffusion test.